2003
DOI: 10.1542/peds.112.3.e248
|View full text |Cite
|
Sign up to set email alerts
|

Successful Endovascular Therapy for Acute Basilar Thrombosis in an Adolescent

Abstract: ABBREVIATIONS. CT, computed tomography (scan); MRI, magnetic resonance imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 47 publications
1
55
0
Order By: Relevance
“…This study reported favorable outcomes in the endovascular treatment group as compared with controls 54 . Combined angioplasty and thrombolysis, with or without stent placement, has also been used in patients with basilar artery occlusion 55,56 .…”
Section: Angioplasty and Stentingmentioning
confidence: 99%
“…This study reported favorable outcomes in the endovascular treatment group as compared with controls 54 . Combined angioplasty and thrombolysis, with or without stent placement, has also been used in patients with basilar artery occlusion 55,56 .…”
Section: Angioplasty and Stentingmentioning
confidence: 99%
“…81,82,83,84,85 In adults the absolute risk reduction for poor outcome is approximately 15% with thrombolysis, with a number needed to treat of 7-8 in the largest RCCT. 86 Careful patient selection and adherence to protocol are critical to optimize the risk:benefit balance of thrombolytic therapy in adults 87,88 but no studies in pediatric stroke have been completed..…”
Section: Hyperacute Treatment: Thrombolysismentioning
confidence: 99%
“…89 Alternative acute in-terventions including mechanical clot manipulation and cerebral angioplasty have only been described in isolated pediatric cases. 84,90 In the case of severe CSVT, the role of catheter-introduced administration of thrombolytics agents remains controversial and could be considered a last resort for children with severe, progressive disease who are failing systemic anticoagulation.…”
Section: Hyperacute Treatment: Thrombolysismentioning
confidence: 99%
“…Recently 2 cases were reported in which children with vertebrobasilar thrombosis benefited from rtPA therapy up to 36 hours after symptom onset. 7,8 Despite the high risk of complications, the poor natural history of basilar artery occlusion in both cases justified the aggressive treatment approach.…”
Section: P R Ac T I C Ementioning
confidence: 99%